Venous thrombosis in unusual sites: A practical review for the hematologist. (29th October 2018) - Shatzel, Joseph J.; O'Donnell, Matthew; Olson, Sven R.; Kearney, Matthew R.; Daughety, Molly M.; Hum, Justine; Nguyen, Khanh P.; DeLoughery, Thomas G.
Abstract: Thrombosis of unusual venous sites encompasses a large part of consultative hematology and is encountered routinely by practicing hematologists. Contrary to the more commonly encountered lower extremity venous thrombosis and common cardiovascular disorders, the various thromboses outlined in this review have unique presentations, pathophysiology, workup, and treatments that all hematologists should be aware of. This review attempts to outline the most up to date literature on cerebral, retinal, upper extremity, hepatic, portal, splenic, mesenteric, and renal vein thrombosis, focusing on the incidence, pathophysiology, provoking factors, and current recommended treatments for each type of unusual thrombosis to provide a useful and practical review for the hematologist.